(-1/3*a^3*b^2)^2*(-2*a*b^2)^3/(1/9*a^4*b^4)^3 = -648/(a^3*b^2)((x+y)^2-(x+y)*(x-y))*2*y = 4*y^3+4*x*y^2x^3*y-6*x^2*y^2+9*x*y^3 = x*y*(3*y-x)^2 (a^2+4*b^2)^2-16*a^2*b^2 ...
(-1/3ab)(-2ab)÷(1/9a^4b^4) [(x+y)-(
1个回答
相关问题
-
计算:(______)•3ab2=9ab5;-12a3bc÷(______)=4a2b;(4x2y-8x3)÷4x2=_
-
(1)x3•3x•x4;(2)(3a2b-2ab2-ab)÷(-ab);(3)2(y6)2+(-y4)3;(4)6x2-
-
①[(x+y)^2-(x+y)(x-y)]/2y②(-1/3a^3b^2)^2(-2ab^2)^3/(1/9a^4b^4
-
1、(18ab^2-9a^5b)÷(-3ab)=___ 2、( )*(-4ab^2)=12a^3b^2c 3、[(a+b
-
X^-9Y^-6Y-1X^-9Y^-6Y+2X(1-A^-B^/A+2B*A^+4AB+4B^/A^-B^)*(A/B*
-
合并同类项:(1)x-y+5x-4y (2)2/3a-1/2ab+3/4a+ab-b (3
-
1.计算 (1)(2a^2 b^2c)^4z÷(-2ab^2c^2)^2 (2) (3x^3y^3z)^4÷(3x^3y
-
1.计算 (1)(2a^2 b^2c)^4z÷(-2ab^2c^2)^2 (2) (3x^3y^3z)^4÷(3x^3y
-
计算:(1)[a+9b/3ab−a+3b3ab](2)x2−1(x−1)2÷1x−1•1x+1.
-
【1】7a-3a 【2】4X^2+2X^ 【3】5ab^2-13ab^2 【4】-9X^2y^3+9X^2y^3